Description of the mature larva of Gonioctena pseudogobanzi Kippenberg, 2001 (Coleoptera: Chrysomelidae: Chrysomelinae) and key to the larvae of the subgenus Spartoxena - Baselga, Andrés (Zootaxa, 2008)
Mature larva of Gonioctena (Spartoxena) pseudogobanzi Kippenberg, 2001 is described and illustrated for the first time, based on specimens collected on Genista umbellata (L’Hér.) Dum. Cours. [Fabaceae] in southeastern Spain. Diagnostic characters for the identification of species within the subgenus Sparoxena Motschulsky, 1860 are number of dorsal tubercles of abdominal segments, shape of tarsal claw, shape of labrum and disposition of microtrichia of epipharynx. A key to known larvae of subgenus Spartoxena is provided, along with figures illustrating the diagnostic characters. Notes on the distribution and host plant of G. pseudogobanzi are included.